Minat Beli Konsumen: Kualitas Pelayana, Kualitas Produk dan Peran mediasi Kepuasan Konsumen - Rahma Sinurat; Deka Wulandari; Elza Nitami Harahap; Mutiara Syahna; Muhammad Irfan Nasution (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2023)
Buying interest has a good effect on sellers and entrepreneurs. Researchers have done much testing on how to increase buying interest among the public. From this research, we aim to find out that buying interest will have influence by good service quality and appropriate product quality which will make consumers feel satisfied, which results in repurchasing interest. With an infinite population, researchers must use purposive sampling to get 30 samples in analyzing the hypothesis using SEM-PLS calculations in the SmartPLS application. The test results found that the influence of service quality on purchase intention was significant. In contrast, for product quality and testing, the three variables produced a value that did not affect purchase intention. This research can help sellers and employers increase buying interest among the public. The level of competition in increasing sales makes sellers have to think about attracting consumers. Improving service quality can initially make people interested in buying at the Sukaramai Medan market.